2019
DOI: 10.1016/s1473-3099(19)30297-x
|View full text |Cite
|
Sign up to set email alerts
|

Pneumococcal lineages associated with serotype replacement and antibiotic resistance in childhood invasive pneumococcal disease in the post-PCV13 era: an international whole-genome sequencing study

Abstract: Background Invasive pneumococcal disease remains an important health priority owing to increasing disease incidence caused by pneumococci expressing non-vaccine serotypes. We previously defined 621 Global Pneumococcal Sequence Clusters (GPSCs) by analysing 20 027 pneumococcal isolates collected worldwide and from previously published genomic data. In this study, we aimed to investigate the pneumococcal lineages behind the predominant serotypes, the mechanism of serotype replacement in disease, as well as the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
199
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 201 publications
(214 citation statements)
references
References 46 publications
15
199
0
Order By: Relevance
“…65 Irrespective of the mechanisms that may be operative in the setting of pneumococcal, nonvaccine serotype antibiotic resistance in particular, the findings of a very recently reported international whole-genome sequencing study are noteworthy. 66 This study was focused on pneumococcal lineages associated with serotype replacement and antibiotic resistance based on whole genome sequencing of strains of the pathogen isolated from children aged <3 years hospitalized with IPD in the pre-and postimmunization periods. 66 The authors reported a significant increase in the prevalence of resistance to penicillin in nonvaccine serotypes in the post-PCV period relative to the pre-PCV13 period (29 vs. 21%, Fig.…”
Section: Causes and Mechanisms Of Antibiotic Resistancementioning
confidence: 99%
See 1 more Smart Citation
“…65 Irrespective of the mechanisms that may be operative in the setting of pneumococcal, nonvaccine serotype antibiotic resistance in particular, the findings of a very recently reported international whole-genome sequencing study are noteworthy. 66 This study was focused on pneumococcal lineages associated with serotype replacement and antibiotic resistance based on whole genome sequencing of strains of the pathogen isolated from children aged <3 years hospitalized with IPD in the pre-and postimmunization periods. 66 The authors reported a significant increase in the prevalence of resistance to penicillin in nonvaccine serotypes in the post-PCV period relative to the pre-PCV13 period (29 vs. 21%, Fig.…”
Section: Causes and Mechanisms Of Antibiotic Resistancementioning
confidence: 99%
“…66 This study was focused on pneumococcal lineages associated with serotype replacement and antibiotic resistance based on whole genome sequencing of strains of the pathogen isolated from children aged <3 years hospitalized with IPD in the pre-and postimmunization periods. 66 The authors reported a significant increase in the prevalence of resistance to penicillin in nonvaccine serotypes in the post-PCV period relative to the pre-PCV13 period (29 vs. 21%, Fig. 1 Exposure of both antibiotic-susceptible (A) and erm(B) macrolide resistance gene-expressing (B) strains of the pneumococcus (depicted as ) to cigarette smoke results in induction of genes which trigger biofilm formation and expression of an ABC transporter, seemingly involved in efflux of antibiotics.…”
Section: Causes and Mechanisms Of Antibiotic Resistancementioning
confidence: 99%
“…Furthermore, this cohort is a mix of sequences isolated from both asymptomatic carriage and disease, whereas SPARC and Maela contain only asymptomatic carriage. The GPS cohort is enriched with more virulent strains, which have more frequently faced treatment with antibiotics, and have a higher rate of resistance (1,63) .…”
Section: Variant Typementioning
confidence: 99%
“…Latex agglutination is an alternative, and a cheaper option than Quellung reaction, but also requires culture of the isolates. Alternative typing methods not based in antisera are described for S. pneumoniae using DNA molecular methods: multiplex PCR [14][15][16], real-time PCR, microchip, sequencing-typing, reverse-hybridization, MALDI-TOF MS, and whole genome sequencing [8,[17][18][19].…”
Section: Introductionmentioning
confidence: 99%